Socio-demographic Characteristics of Surgically Resected Histopathological Confirmed Intestinal Tuberculosis Patients attended at a Tertiary Care Hospital in Dhaka City (Bangladesh Journal of Infectious Diseases, 2022)
Background: Intestinal tuberculosis can occur in different socio-demographic characteristics.Objective: The purpose of the present study was to see socio-demographic characteristics of surgically resected histopathological confirmed intestinal tuberculosis patients.Methodology: This cross-sectional study was conducted at the Department of surgery, Dhaka Medical College hospital, Dhaka from July 2005 to December 2007 for a period of two and a half year. Purposive sampling was followed as per inclusion and exclusion criteria. The patients were evaluated based on history, physical examination, laboratory investigations and other relevant investigations.Result: Total numbers of cases in this series were 50 cases. The youngest patient of the series was 15 years and the oldest was 60 years. The average age of the patients was 34.5±12.6 years. Out of 50 patients 64.0% cases were male and 36.0% cases are female with a male to female ratio 1.77:1. Most of the patients were farmer which was 52.0% cases. In this study 37(74.0%) cases came from lower socio-economic condition. Majority cases were in poor nutritional status (84.0%) and came from rural area (56.0%). In this study 40.0% patients were vaccinated and 50.0% cases were smoker.Conclusion: In conclusion adult middle age male farmers with low-socioeconomic condition patients are most commonly suffering from intestinal tuberculosis.Bangladesh Journal of Infectious Diseases June 2021;8(1):7-11